A Survey on Students' Homework Practice and Attitudes towards English Homework - Chong, Nyok Moi (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study sought to investigate the homework practice and attitudes towards English homework by lower form (Transition or Form One) and upper form (Form Four or Form Five) students in five secondary schools in Kuching district. The aspects that the study aimed to look into are the amount of time spent on homework in general and on English homework, students' purposes of doing English homework, types of English homework and types of feedback given by English teachers. The study was conducted in cross-sectional survey research using questionnaires. A total of 197 respondents were chosen from the five selected schools. The findings showed the amount of time students spent on homework in general and on English homework was moderate. The students had positive views towards purposes of doing English homework even though their homework mostly involved traditional written tasks. They also had positive attitudes towards English homework and there was no indication that their attitudes differed in relation to genders, academic performance and level form of students.